Depleted Plasma Densities in the Ionosphere of Venus Near Solar Minimum From Parker Solar Probe Observations of Upper Hybrid Resonance Emission. Issue 9 (3rd May 2021) - Collinson, Glyn A.; Ramstad, Robin; Glocer, Alex; Wilson, Lynn; Brosius, Alexandra
Abstract: On July 11, 2020, NASA's Parker Solar Probe made its third flyby of Venus. The upper hybrid resonance emission was observed below 1, 100 km (a first at Venus), revealing electron densities an order of magnitude lower than at solar maximum. These observations are consistent with a substantial variation in the density and structure of the Venusian ionosphere over the Solar Cycle. Plain Language Summary: The planet Venus is in many ways the most Earth‐like planet known and is thus a perfect natural laboratory for understanding what makes Earth‐like planets habitable. It is often thought that Earth's magnetic field is important for life to exist, as it shields our atmosphere from being stripped away to space. If this is true then one might expect that Venus, with no protective magnetic field, would lose more atmosphere when the sun was more active. However, recent studies have shown the opposite to be true. To investigate this, we need measurements of the upper most part of the Venusian atmosphere (the ionosphere, the source of atmospheric escape. On July 11, 2020, NASA's Parker Solar Probe made a close flyby of Venus. During the 7 minutes around the closest approach, one of its scientific instruments detected low‐frequency radio emission of a type naturally generated by planetary ionospheres. By measuring the frequency of this emission, we can directly calculate the density of the ionosphere around Parker, finding it to be far less dense than previous missions have encountered. This supports the theory that the ionosphere of Venus varies substantially over the 11 year solar cycle. Key Points: We report the first detection of upper hybrid resonance emission at Venus, the first in situ measurement of the ionosphere at solar minimum Electron densities were an order of magnitude lower than at solar maximum, and asymmetrically denser toward the terminator The Venusian ionosphere varies significantly over the solar cycle, confirming past remote sensing experiments